The Rhythm of Change A Longitudinal Analysis of the European Insurance Industry - Klarner, Patricia; SpringerLink (Online service) (Wiesbaden : Gabler, 2010)
Strategic change management is indispensable for every organization that has to adjust its strategy to changing industry contexts. Patricia Klarner adopts a new approach to analyze strategic changes and introduces the rhythm of change as a concept that measures the timing of changes. Her research model examines the relationship between the rhythm of change and long-term firm performance as well as the impact of knowledge-related and financial moderators on this relationship. It is empirically tested in the European insurance industry for the period from 1995 to 2004. The author provides a state-of-the-art view of the optimal timing of strategic changes in organizations and of the factors underlying successful change efforts.
Literature Review -- The Rhythm of Strategic Change: Towards a Comprehensive Research Model -- Research Methodology -- Research Findings -- Conclusion.
Keywords: Economics; Industrial management; Economics/Management Science; Management/Business for Professionals